Rabies virus nucleoprotein: Large-scale expression in prokaryotic system - Picotto, Leandro Daniel (2024)
Rabies is controlled by mass animal vaccination campaigns. Cats, dogs, and wild animals (e.g., bats) are large reservoirs of this virus and can pose a significant threat to the human health, especially in the developing countries. The nucleoprotein of the rabies virus is of great scientific interest since it has the potential to generate immunity in animals and can be used as for immunochemical diagnostics. The study aimed to test a large-scale expression of the rabies N protein in a prokaryotic system. The recombinant N protein was successfully expressed and purified. It was immunologically recognized by specific antibodies and was able to induce the production of specific antibodies in a mouse immunization assay. These encouraging results indicate that the recombinant N protein can be evaluated as an antigen for the development of a subunit vaccine or for a diagnostic assay.